The landscapes of Anne of Green Gables : the enchanting island that inspired L.M. Montgomery - Reid, Catherine, 1955- (Timber Press, 2018)
From the Lake of Shining Waters and the Haunted Wood to Lover's Lane, readers will be immersed in the real places immortalized in the novel "Anne of Green Gables." Using Montgomery's journals, archives, and scrapbooks, Catherine Reid explores the many similarities between Montgomery and her unforgettable heroine, Anne Shirley. The lush package includes Montgomery's hand-colourized photographs, the illustrations originally used in Anne of Green Gables, and contemporary and historical photography. Print run 25,000.